Diseño urbano de una planta de reciclaje de desechos plásticos en la zona Parque Industrial en Ibarra - Ortega Játiva, Katherine Patricia (2024)
This degree work is located northwest of the capital of Imbabura, in the city of Ibarra, in the only industrial zone that the city has. This degree work focuses on the urban design of a plastic waste recycling plant in the Ibarra industrial park area. The main objective is to efficiently integrate the recycling plant into the urban environment, taking into account technical standards, the environment and mobility. The study aims to develop proposals to integrate the strategic location of recycling cooperatives, the planning of transport routes and the sustainability of the city, with the aim of promoting the sustainable management of plastic waste in the city of Ibarra and community participation, technical standards for the necessary infrastructure will also be considered.